Iluraton fortress in the context of military actions on the western borders of the Bosporan Kingdom in the 1st–3rd centuries AD - Goroncharovskiy, Vladimir A. (City and War, 2021)
Excavations of Iluraton give a vivid idea of the life of the garrison of a small fortress on the western approaches to Panticapaeum, the capital of the Bosporan kingdom, and the level of development of the local fortification of the Roman period. The earliest building remains of Iluraton of the middle of the 1st century AD are a small tower with an adjacent section of the defensive wall and a well with an underground passage. This fortress did not last long and was destroyed several decades later during the military conflicts between the Bosporus and the Late Scythians. The reconstruction of the defensive lines of Iluraton is carried out not earlier than the second third of the 2nd century AD. At the end of this century, when the military and political situation on the western borders of the Bosporus worsened again, a radical reconstruction of the entire territory of urban development took place. The three fortress walls were further strengthened at the base by an anti-ram belt. Another obstacle was created by a moat cut into the rock to a depth of 1.5 m. The last stage was the construction in the first third of the 3rd century AD of a strip of residential development behind the north-western defensive wall. During attack narrow passages between houses were laid, creating an additional obstacle in the way of the enemy. New information about this period was obtained in 2013, when it became possible to record the eastern corner of the fortress – a semicircular bastion with a diameter of about 8 m carried down the hill. At the beginning of the second half of the 3rd century all the fortifications were seriously damaged by the destruction caused by the powerful earthquake. Soon after Iluraton ceased to exist due to the events of the period of the Gothic Wars.